Predictive value of cardiovascular parameters in twin‐to‐twin transfusion syndrome. (October 2014) - Gapp‐Born, E.; Sananes, N.; Weingertner, A. S.; Guerra, F.; Kohler, M.; Fritz, G.; Viville, B.; Gaudineau, A.; Langer, B.; Sauleau, E.; Nisand, I.; Favre, R.
ABSTRACT Objective To evaluate the prognostic value of the Children's Hospital Of Philadelphia (CHOP) cardiovascular score and the modified myocardial performance index (MPI), in determining the risk of recipient fetal loss in twin‐to‐twin transfusion syndrome (TTTS). Methods This cohort study was based on data collected prospectively from 105 pregnancies complicated by TTTS (Quintero stages I–IV) and treated with laser photocoagulation between May 2008 and February 2013. Fetuses underwent detailed anatomical and Doppler ultrasonography with cardiac assessment as part of routine care. CHOP score and right MPI were calculated and cut‐offs selected using receiver–operating characteristics curve analysis. These were compared according to loss of recipient fetus, using univariate and multivariate logistic regression. The correlation between CHOP score, MPI and Quintero stage was determined and we investigated differences in MPI before and after laser coagulation in a cohort of 90 recipient fetuses. Results Rates of recipient fetal loss were significantly higher when the CHOP score was ≥ 3 (39.5% vs 12.9%, P = 0.002) and when MPI z‐score was > 1.645 (34.5% vs 10.6%, P = 0.004). After adjustment for Quintero stage, the risk of recipient fetal loss remained significantly higher when the CHOP score was ≥ 3 (odds ratio, 3.09; 95% CI, 1.035–9.21). There was a positive correlation between CHOP score, MPI and Quintero stage. MPI was significantly lower after compared with before laser coagulation. Conclusion CHOP score and MPI are predictors of recipient fetal loss in TTTS and may be used to supplement Quintero's classification. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.